The propagation of spiraling elliptic sine soliton in nonlocal nonlinear media - Rui Liu (Results in Physics, 2018)
We study a novel spiraling elliptic sine soliton (SESS) in nonlocal nonlinear media by split-step Fourier method, and find that the profile and phase of such soliton have complicated structures. Numerical results show that the topological charge and ellipticity have profound effects on the propagation dynamics of SESS. Concretely, for the same ellipticity, the different topological-charge SESS have the same critical power, cross-term phase coefficient, rotation period, and different critical orbital angular momentums (OAM). However, the critical power, cross-term phase coefficient, rotation period and OAM will increase as the increase of ellipticity. In addition, as the ellipticity and topological charge increase, the stability of the beam will decrease. Keywords: Nonlinear optics, Nonlocal media, Spiraling elliptic sine soliton